Countermovement jump and momentum generation associations to fastball velocity performance among Division I collegiate pitchers - Sakurai, M.; Qiao, M.; Szymanski, D. J.; Crotin, R. L. (The Journal of Strength and Conditioning Research, 2024)
The current study explored the relationships between countermovement jump (CMJ) profiles and baseball pitching performance. Nineteen Division I collegiate pitchers performed in-laboratory pitching and bilateral CMJs. Whole-body kinematics and ground reaction force were collected during both pitching and CMJ evaluations. Statistically significant correlations of concentric impulse and peak power in the CMJ test with fastball velocity were observed (r = 0.71 and 0.68). Concentric impulse in CMJ also showed a statistically significant correlation with linear momentum in the anterior-posterior direction during pitching (r = 0.68). Lean body mass and body mass showed statistically significant correlations with both of the 2 linear momentums during pitching (r = 0.71~0.83), and concentric impulse in CMJ (r = 0.71 and 0.81). Pelvis and trunk pitching mechanics did not correlate with any of the CMJ variables at the statistically significant level, whereas the direction of the correlations varied (|r| < 0.45). Assessment of a baseball pitcher's CMJ should focus on concentric impulse and peak power because only these showed meaningful relationships with fastball velocity or momentum generation during pitching. An increase in lean body mass is also suggested to be able to generate more impulse and momentum. Baseball coaches, strength coaches, and clinicians are encouraged to include lower-body explosive training to enhance the force and power output capacity of baseball pitchers.